2007
DOI: 10.1158/0008-5472.can-07-1267
|View full text |Cite
|
Sign up to set email alerts
|

Selective Role of an NH2-Terminal WxxLF Motif for Aberrant Androgen Receptor Activation in Androgen Depletion–Independent Prostate Cancer Cells

Abstract: Systemic prostate cancer therapy requires androgen ablation, which inhibits the production or action of androgens. Prostate cancer ultimately relapses during androgen ablation, and an androgen depletion-independent (ADI) phenotype emerges. Aberrant androgen receptor (AR) activation underlies therapy resistance at this stage of the disease, and mounting evidence implicates the large and highly disordered AR NH 2 -terminal domain (NTD) as a key mediator of this activity. In this study, we investigated the role o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(79 citation statements)
references
References 42 publications
3
76
0
Order By: Relevance
“…Two epidemiologic studies examined polymorphic variants of the AR gene and its coactivator AIB1 in cases and controls, with mixed results (11,21). Studies on androgen receptor coactivators in prostate cancer showed that androgen receptor coactivators are associated with disease aggressiveness and poor prognosis (22), with androgen receptor activation related to androgen-refractory disease (23), and with resistance to antiandrogen (24,25). The role of androgen receptor corepressors in prostate cancer is not yet well-defined.…”
Section: Androgenic Action In the Prostatementioning
confidence: 99%
“…Two epidemiologic studies examined polymorphic variants of the AR gene and its coactivator AIB1 in cases and controls, with mixed results (11,21). Studies on androgen receptor coactivators in prostate cancer showed that androgen receptor coactivators are associated with disease aggressiveness and poor prognosis (22), with androgen receptor activation related to androgen-refractory disease (23), and with resistance to antiandrogen (24,25). The role of androgen receptor corepressors in prostate cancer is not yet well-defined.…”
Section: Androgenic Action In the Prostatementioning
confidence: 99%
“…2) implicated in the androgen-dependent AR N/C interaction and transcriptional activity (13,(21)(22)(23). Expression studies using wild-type and mutant AR and select AR fragments ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The AR N/C interaction is modulated by primate-specific melanoma antigen-A11 (MAGE-11) that binds the AR FXXLF motif and functions synergistically with the AR N/C interaction, coregulators, and transcription factors (16 -20). An AR NH 2 -terminal WXXLF motif contributes to the AR N/C interaction through mechanisms not well understood (21,22). Disruption of the AR N/C interaction by mutating the AR NH 2 -terminal FXXLF motif inhibits AR transcriptional activation of androgen-responsive reporter genes (23).…”
Section: The Androgen Receptor (Ar)mentioning
confidence: 99%
See 1 more Smart Citation
“…In the LBD, the binding of androgen hormone to AR is promoted [8]. AF2 domain in the LBD interacts with co-regulators with LXXLL motif [9][10][11]. In the absence of hormone, AR forms a complex in the cytoplasm with the heat shock protein (Hsp) family that functions as molecular chaperones.…”
Section: The Androgen Receptor (Ar) Functions As a Nuclear Receptor Tmentioning
confidence: 99%